Experience of Pediatricians and Pediatric Surgeons With Virtual Care During the COVID-19 Pandemic: Descriptive Study - Emma McCrady; Julie E Strychowsky; Jessica P Woolfson (JMIR Publications, 2022)
BackgroundPrior to the COVID-19 pandemic, in-clinic visits were the standard of care for pediatric physicians and surgeons at our center. At the pandemic onset, web-based care was adopted at an unprecedented scale and pace. ObjectiveThis descriptive study explores the web-based care experience of pediatric physicians and surgeons during the pandemic by determining factors that supported and challenged web-based care adoption. MethodsThis study took place at the Children's Hospital at London Health Sciences Centre, a children's hospital in London, Ontario, Canada, which provides pediatric care for patients from the London metropolitan area and the rest of Southwestern Ontario. The Donabedian model was used to structure a web-based survey evaluating web-based care experience, which was distributed to 121 department-affiliated pediatric physicians (including generalists and subspecialists in surgery and medicine). Recruitment occurred via department listserv email. Qualitative data were collected through discrete and free-text survey responses. ResultsSurvey response rate was 52.1% (63/121). Before the pandemic, few physicians within the Department of Paediatrics used web-based care, and physicians saw <10% of patients digitally. During March-May 2020, the majority transitioned to web-based care, seeing >50% of patients digitally. Web-based care use in our sample fell from June to September 2020, with the majority seeing <50% of patients digitally. Telephone and Ontario Telemedicine Network were the platforms most used from March to September 2020. Web-based care was rated to be convenient for most providers and their patients, despite the presence of technical difficulties. Challenges included lack of physical exam, lower patient volumes, and poor patient digital care etiquette. Regardless of demographics, 96.4% (116/121) would continue web-based care, ideally for patients who live far away and for follow-ups or established diagnoses. ConclusionsTransition to web-based care during COVID-19 was associated with challenges but also positive experiences. Willingness among pediatricians and pediatric surgeons to continue web-based care was high. Web-based care experiences at our center could be improved with patient education and targeting select populations. Future research is needed to improve practice efficiency and to inform regulatory guidelines for web-based care.